2009
DOI: 10.1186/2047-783x-14-10-433
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen exposure, obesity and thyroid disease in women with severe pulmonary hypertension

Abstract: Severe pulmonary hypertension is a lethal group of disorders which preferentially afflicts women. It appears that in recent years the patient profile has shifted towards older, obese, and postmenopausal women, suggesting that endocrine factors may be important. Several studies have revealed an increased prevalence of thyroid disease in these patients, but no studies have evaluated for a coexistence of endocrine factors. In particular, no studies have attempted to evaluate for concurrent thyroid disease, obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…To date, sex remains the most powerful modifier of disease development, as demonstrated by the high prevalence of IPAH in females between the age of 35 and 50 years. Some clinical studies of PAH indicated that abnormalities in estrogen metabolism may play a pathogenic role of PAH [10]. In contrast to these clinical studies, most animal studies have shown that female sex and estrogen supplementation can have a protective effect against PAH.…”
Section: Discussionmentioning
confidence: 87%
“…To date, sex remains the most powerful modifier of disease development, as demonstrated by the high prevalence of IPAH in females between the age of 35 and 50 years. Some clinical studies of PAH indicated that abnormalities in estrogen metabolism may play a pathogenic role of PAH [10]. In contrast to these clinical studies, most animal studies have shown that female sex and estrogen supplementation can have a protective effect against PAH.…”
Section: Discussionmentioning
confidence: 87%
“…However, it seems to contradict the female predominance that is observed in idiopathic PAH. Moreover, Sweeney and Voelkel (49) showed that early and long term estrogen exposure might be correlated with an increased risk of the development of PAH (49). Here we ask the question: Is estrogen a friend or a foe?…”
mentioning
confidence: 97%
“…Thus, the female predominance in PAH and the adverse effects of estrogen suggest that this hormone has the theoretical potential to negatively affect PAH. A heterogenous cohort of obese women with pulmonary hypertension reported an unusually high incidence of exogenous estrogen use (49), further complicating the interpretation of estrogen's effects on the pulmonary vascular disease. Unfortunately, definitive epidemiological studies about the risks of exogenous estrogens in PAH are near impossible given the rare nature of the disease and its predilection for the young.…”
mentioning
confidence: 99%
“…Estrogen-induced rescue of severe pre-existing PH seems to be associated with stimulation of cardiopulmonary neoangiogenesis, suppression of inflammation, fibrosis and right ventricular hypertrophy, most likely mediated through ER-β [23]. Human studies in postmenopausal women also suggest a protective role of estrogen in PH [24,25]; nevertheless, contradictory data exist [26,27]. Interestingly, the only publication on the use of ART in a patient with primary pulmonary hypertension did not report any complications [28].…”
Section: Discussionmentioning
confidence: 99%